2017
DOI: 10.1080/10903127.2017.1308607
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Associated with Prehospital “Lift-assist” Calls

Abstract: LA calls are associated with short-term morbidity and mortality. Patient age was found to be associated with these outcomes. These calls may be early indicators of problems requiring comprehensive medical evaluation and thus further factors associated with poor outcomes should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…6 In addition, lift-assist calls are associated with increased morbidity and mortality within 14 days of a lift-assist call. 7 Emerging evidence indicates that the “lift assist” call should be considered a sentinel event and perhaps serve as a trigger for additional assessment and intervention to prevent injury, medical deterioration, and disability to older patients within a community. 8 …”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, lift-assist calls are associated with increased morbidity and mortality within 14 days of a lift-assist call. 7 Emerging evidence indicates that the “lift assist” call should be considered a sentinel event and perhaps serve as a trigger for additional assessment and intervention to prevent injury, medical deterioration, and disability to older patients within a community. 8 …”
Section: Introductionmentioning
confidence: 99%
“…2 In Dr. Leggatt's study, 14% percent of the ambulance call reports for lift-assist patients were missing at least one vital sign-primarily temperatureand more than a quarter of patients with a history of diabetes did not have a documented blood glucose level. 1 One interpretation of this finding is that many patients were inadequately assessed, with the presumption that better assessment might have identified patients at risk and prevented some of the subsequent ED visits, hospitalizations and/or deaths. Another possibility is that some patients simply refused detailed assessment once the lift-assist was complete.…”
Section: Commentary Researching Lift-assists: Nebulous Complexitymentioning
confidence: 99%
“…In both studies, approximately one in five lift-assist patients had a subsequent ED visit, 1,2 and this newest study reported one in eight lift-assist patients were subsequently hospitalized. 1 What we don't know is how the rates of repeat EMS calls, ED visits and hospitalizations in the lift-assist population compare to those of simple fall patients who are transported to hospital, or to those of other non-transport patients, or to those of the elderly population in general. In the absence of a randomized controlled trial in which lift-assist patients are allocated to transport and non-transport cohorts, what is the most appropriate comparison group for evaluating outcomes of lift-assist patients?…”
Section: Commentary Researching Lift-assists: Nebulous Complexitymentioning
confidence: 99%
See 2 more Smart Citations